Salvage Therapy of Multiple Myeloma: The New Generation Drugs. (19th May 2014) - Romano, Alessandra; Conticello, Concetta; Cavalli, Maide; Vetro, Calogero; Di Raimondo, Cosimo; Di Martina, Valentina; Schinocca, Elena; La Fauci, Alessia; Parrinello, Nunziatina Laura; Chiarenza, Annalisa; Di Raimondo, Francesco
Abstract : During the past decade, overall results of treatment of multiple myeloma (MM) have been improved and survival curves are now significantly better with respect to those obtained with historical treatment. These improvements are linked to a deeper knowledge of the biology of disease and to the introduction in clinical practice of drugs with different mechanism of action such as proteasome inhibitors and immunomodulatory drugs (IMiDs). However, MM remains in most cases an incurable disease. For patients who relapse after treatment with novel agents, the prognosis is dismal and new drugs and therapeutic strategies are required for continued disease control. In this review, we summarize new insights in salvage therapy for relapsed/refractory MM as emerging from recent clinical trials exploring the activity of bendamustine, new generation proteasome inhibitors, novel IMiDs, monoclonal antibodies, and drugs interfering with growth pathways.